1996
DOI: 10.1002/j.1460-2075.1996.tb00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence of Saccharomyces cerevisiae chromosome X.

Abstract: The complete nucleotide sequence of Saccharomyces cerevisiae chromosome X (745 442 bp) reveals a total of 379 open reading frames (ORFs), the coding region covering approximately 75% of the entire sequence. One hundred and eighteen ORFs (31%) correspond to genes previously identified in S. cerevisiae. All other ORFs represent novel putative yeast genes, whose function will have to be determined experimentally. However, 57 of the latter subset (another 15% of the total) encode proteins that show significant ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 46 publications
(43 reference statements)
1
44
0
Order By: Relevance
“…This may be due to the limitations of available methods for recovering subtle functions and to functional redundancy with other genes. The extensive gene duplication within the S. cerevisiae genome revealed by the systematic sequencing confirms the second notion (Feldmann et al, 1994;Galibert et al, 1996). In the case of the three non-essential genes reported here, which have no duplicate in the rest of the genome, viable haploid segregants bearing the deletion mutations were tested for growth characteristics, heat sensitivity, cold sensitivity, ability to mate, and sporulation frequencies.…”
Section: Discussionsupporting
confidence: 62%
“…This may be due to the limitations of available methods for recovering subtle functions and to functional redundancy with other genes. The extensive gene duplication within the S. cerevisiae genome revealed by the systematic sequencing confirms the second notion (Feldmann et al, 1994;Galibert et al, 1996). In the case of the three non-essential genes reported here, which have no duplicate in the rest of the genome, viable haploid segregants bearing the deletion mutations were tested for growth characteristics, heat sensitivity, cold sensitivity, ability to mate, and sporulation frequencies.…”
Section: Discussionsupporting
confidence: 62%
“…In vertebrates, initiation at non-AUG sites of some mRNAs can also be stimulated in the presence of specific nucleotides located downstream of the initiation codon, preferentially G at þ4, A or C at þ5 and U at þ6 (Grü nert and Jackson, 1994). Interestingly, this experimentally derived optimal downstream sequence is similar although not identical to the statistically derived preferential use of downstream nucleotides between positions þ4 and þ6 (GCU) of yeast and plant mRNAs (Galibert et al, 1996;Koziel et al, 1996).…”
Section: 'Consensus Sequences' That Influence the Selection Of Initiamentioning
confidence: 83%
“…GCU) found in yeast and plant mRNAs ( Fig. 2B; Galibert et al, 1996;Koziel et al, 1996) may help to correctly position a potential initiation codon in the decoding centre. Interestingly, the core region of the 18S rRNA decoding centre is nearly identical to the sequences in and around the anticodon loop of initiator tRNA (Fig.…”
Section: Internal Ribosome Entry: An Alternative Mechanism For Selectmentioning
confidence: 99%
“…3). Sequence analysis of the inserts of these two plasmids indicated that they were overlapping genomic fragments from yeast chromosome X (11) and that each contained two ORFs of unknown function, YJL055W and YJL056C. A 4-bp frameshift mutation introduced into the BssHII site of YJL056C eliminated both the His ϩ and uptake phenotypes, whereas a similar mutation introduced into the MluI site of YJL055W had no effect.…”
Section: Resultsmentioning
confidence: 99%